"Squandered in Real Time": How Public Management Theory Underestimated the Public Administration–Politics Dichotomy. Issue 6 (August 2020) - Young, Sarah L.; Wiley, Kimberly K.; Searing, Elizabeth A. M.
The United States places great emphasis on the public administration–politics dichotomy, but what happens to public management when the dichotomy breaks down? The authors critically evaluate the public management frameworks, New Public Management and New Public Governance, in the context of two major public management failures: the U.S. State of Illinois Budget Impasse during 2015–2017 and the COVID-19 Pandemic. A definition of public management failure is proffered, and both public management frameworks are found to have polarized and opposing views on whether process or outcome should have priority in crisis. We question whether the two major seminal theories in our field are still generalizable when their assumptions about the dichotomy and political neutrality are challenged in times of crises. The polarized perspectives were found to contribute to the public management failures. Ultimately, both frameworks were found to minimize the political influences that public administration and public management operate under, leaving a need for a more holistic and realistic framework.